2023
DOI: 10.1093/jpepsy/jsad014
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Adolescents With Chronic Pain About Peer Support: Reflexive Thematic Analysis

Abstract: Objective Social challenges are a common experience for adolescents with chronic pain. Group peer support for these adolescents could be a promising intervention; however, no studies have focused exclusively on the peer support needs of this population. The present study addressed this gap in the literature. Methods Adolescents with chronic pain between 12 and 17 years of age completed a virtual interview and demographics que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…17,36 Mirroring our findings, Ahola Kohut et al 37 analyzed the content of peer mentoring calls among adolescents with chronic illnesses and found that the mentors and mentees spoke mostly about nonillness related issues (eg, interests, current events) as well as the impact of their condition on things like relationships and school/work. Given that ACPs perceive GPS as helping to facilitate relationships, 7 this study underscores that although having pain in common may be important, it is not the only thing that ACPs want to connect over. In fact, findings such as these were highlighted in work exploring naturally developing friendships among ACPs attending a self-management program 34 ; only having pain in common was one of the main reasons ACPs did not want to develop friendships with other ACPs.…”
Section: Table 4 (Continued)mentioning
confidence: 87%
See 4 more Smart Citations
“…17,36 Mirroring our findings, Ahola Kohut et al 37 analyzed the content of peer mentoring calls among adolescents with chronic illnesses and found that the mentors and mentees spoke mostly about nonillness related issues (eg, interests, current events) as well as the impact of their condition on things like relationships and school/work. Given that ACPs perceive GPS as helping to facilitate relationships, 7 this study underscores that although having pain in common may be important, it is not the only thing that ACPs want to connect over. In fact, findings such as these were highlighted in work exploring naturally developing friendships among ACPs attending a self-management program 34 ; only having pain in common was one of the main reasons ACPs did not want to develop friendships with other ACPs.…”
Section: Table 4 (Continued)mentioning
confidence: 87%
“…33 ACPs have stated that they need support from other ACPs, given the lack of social support they receive from their peers without pain. 7 The current study explored ACPs' preferences for a GPS intervention. The findings suggest that…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations